"BEST INTEREST" OF WHOM?. Issue 1 (3rd May 2016) - Schaff, Jeffery E.; Schaff, Michele
Abstract : Purpose: Explains the U.S. Department of Labor's newly proposed "Conflicts of Interest" rule and provides a critical analysis of its impact should it be adopted as proposed. Design/methodology/approach: Explains the DOL's proposed Conflict of Interest rule and discusses how it changes the current fiduciary standards of care under ERISA. The article then probes more deeply into the practical matters involved in implementing the rule, and into the realities of how it would impact fiduciary standards generally, as well as investors, the financial services industry and securities arbitrations. Reactions to the proposed rule are then explained against the backdrop of the practical implications thereof. Findings: This article concludes that the DOL's proposed Conflict of Interest rule, albeit well intended, is not reasonably designed to achieve its stated goal and would instead likely harm those whom it purports to help. Ironically, it also potentially waters down the existing high standards of current fiduciaries. The article supports the DOL's goal of greater responsibility for financial service professionals and proffers an alternative solution that could achieve the desired result more effectively. Originality/value: This article offers valuable insight on the realities of the proposed law and practical guidance on its implications to the investing public, the financial services industry and securities attorneys.